Degradable piezoelectric biomaterials for wearable and implantable bioelectronics - Li, Jun; Long, Yin; Yang, Fan; Wang, Xudong (Current opinion in solid state & materials science, 2020)
•An overview of advancements in biodegradable piezoelectric materials was provided.•Attempts to decipher origin of piezoelectricity were introduced.•In vivo and in vitro degradation behaviors are discussed and analyzed.•Implementations of those materials in novel bioelectronics are exemplified.•Challenges together with potential research directions are well summarized. Current bioelectronics are facing a paradigm shift from old-fashioned unrecyclable materials to green and degradable functional materials with desired biocompatibility. As an essential electromechanical coupling component in many bioelectronics, new piezoelectric materials are being developed with biodegradability, as well as desired mechanical and electromechanical properties for the next generation implantable and wearable bioelectronics. In this review, we provide an overview of the major advancements in biodegradable piezoelectric materials. Different natural (such as peptide, amino acids, proteins, cellulose, chitin, silk, collagen, and M13 phage) and synthetic piezoelectric materials (such as polylactic acid) are discussed to reveal the underlying electromechanical coupling mechanism at the molecular level, together with typical approaches to the alignment of orientation and polarization to boost their electromechanical performance. Meanwhile, in vivo and in vitro degradation manners of those piezoelectric materials are summarized and compared. Representative developments of typical electronic prototypes leveraging these materials are also discussed. At last, challenges toward practical applications are pointed out together with potential research opportunities that might be critical in this new materials research area.